Gamma delta T-cell reconstitution after allogeneic HCT: A platform for cell therapy - Gaballa, Ahmed; Arruda, Lucas C. M.; Uhlin, Michael (Frontiers in Immunology, 2022)
Allogeneic Hematopoietic stem cell transplantation (allo-HCT) is a curative platform for several hematological diseases. Despite its therapeutic benefits, the profound immunodeficiency associated with the transplant procedure remains a major challenge that renders patients vulnerable to several complications. It is well established now that a rapid and efficient immune reconstitution, particularly of the T cell compartment is pivotal not only short-term but also for a long-term favorable outcome. T cells expressing a TCR heterodimer comprised of gamma (γ) and delta (δ) chains has been and still is a major focus of research. Due to their unique features, γδ T cells have received particular attention in allo-HCT setting, as a large body of evidence has indicated that γδ T cells can exert favorable potent anti-tumor effects without inducing severe graft versus host disease (GVHD). However, despite their potential role in allo-HCT, studies that investigated their detailed reconstitution in patients undergoing allo HCT are scarce. We aim in this review to shed light on the current literature and understanding of γδ T cell reconstitution kinetics as well as the different transplant-related factors that may influence γδ reconstitution in the allo-HCT setting. Furthermore, we will present data from available reports supporting a favorable role of γδ cells and their subsets in patient outcome. Finally, we will revisit the current and future strategies that aim to develop γδ cell-based therapies that can pave the way for exploiting the full immunotherapeutic potential of γδ cells in HCT setting.